2020
DOI: 10.3390/f11040413
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Forest Spatial Structure with Neighborhood-Based Indices: Four Case Studies from Northeast China

Abstract: The fine-scale spatial patterns of trees and their interactions are of paramount importance for controlling the structure and function of forest ecosystems; however, few management techniques can be employed to adjust the structural characteristics of uneven-aged mixed forests. This research provides an accurate, efficient, and impersonal comprehensive thinning index (P-index) for selecting candidate harvesting trees; the index was proposed by weighting the commonly used quantitative indices with respect to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The developments of horizontal distribution patterns are usually shifted from aggregation to random with forest succession, maintaining the random pattern consistently if the forest community could reach its climax status. Our results indicated that the trees grown in NLF, SEF and KBF stands were all randomly distributed (Table 3), which were perfect in line with the results of Wan et al (2019) and Dong et al (2020); however, slight aggregated distribution was observed for NBF, mainly due to a certain percentage of trees were sprouting regimentation in the stands. Regardless of the distribution pattern, the tree-level harvest 20 optimization could produce significant randomly distributions immediately.…”
Section: Nlf Nbf Sef Kbfsupporting
confidence: 84%
See 4 more Smart Citations
“…The developments of horizontal distribution patterns are usually shifted from aggregation to random with forest succession, maintaining the random pattern consistently if the forest community could reach its climax status. Our results indicated that the trees grown in NLF, SEF and KBF stands were all randomly distributed (Table 3), which were perfect in line with the results of Wan et al (2019) and Dong et al (2020); however, slight aggregated distribution was observed for NBF, mainly due to a certain percentage of trees were sprouting regimentation in the stands. Regardless of the distribution pattern, the tree-level harvest 20 optimization could produce significant randomly distributions immediately.…”
Section: Nlf Nbf Sef Kbfsupporting
confidence: 84%
“…Equation 13 limits the proportion of assigned harvest trees to a range from 𝛼 𝑙 to 𝛼 𝑢 . According to recent published works (Macdonald et al, 2004;Li et al, 2014;Dong et al, 2020) and management practices (State Forestry Bureau, 2016), 𝛼 𝑙 and 𝛼 𝑢 are assumed to be 10% and 40%, respectively. Equation 14 requires that the decision variables are binary.…”
Section: Optimization Formulationsmentioning
confidence: 99%
See 3 more Smart Citations